Antimicrobial potential of ozonized vegetable oils against bacterial species: an integrative review (Research, Society and Development, 2021)
The increasing incidence of bacterial infections in chronic skin lesions is a worldwide problem. Research on alternative therapeutic methods, such as the use of ozonated vegetable oils, has become promising. Thus, it was aimed to evidence the antimicrobial action of ozonized vegetable oils against bacterial strains. This is an integrative review conducted through searches the following databases and libraries: Latin American and Caribbean Health Sciences Literature, Medical Literature Analysis and Retrieval System Online, National Library of Medicine, Scientific Electronic Library Online and two Elsevier databases (Science Direct e Scopus). 11 articles were selected, 73% of these works were published in the last five years, while only 27% were published in 2011 and 2013. There have been publications from China, Italy, Brazil, Cuba, France and Turquey. All studies used laboratory methods to assess the antimicrobial potential of ozonized vegetable oil. The antibacterial effect of the oils was related to the ozonation conditions that were submitted and their final composition of peroxides and carboxylic acids. It was found that these compounds promoted cellular changes and prevented bacterial growth, which could cause bacterial death. Through this review it was possible to present updated information on a promising therapeutic alternative against bacterial skin infections.